Wellington's Army 1809-1814 - Oman, Charles William Chadwick (London Edwrad Arnold, 1913)
This book is a replica, produced from digital images of the original. It was scanned at the University of Toronto Libraries and may contain defects, missing pages or blemishes due to the original source content. The UT libraries have worked with various digital partners to provide the best possible customer experience and hope you enjoy the results.
Includes Illustrations and Index
Keywords: Wellington, Arthur Wellesley, Duke of, 1769-1852 -- Peninsular War (1807-1814)